Anatomical and micromorphological study of Phalaris (Poaceae) species in Iran - Barati, Zahra; Keshavarzi, Maryam; Mosaferi, Samaneh (Acta Biologica Szegediensis, 2025)
The genus Phalaris, comprising 18 species globally, has a complex taxonomic history. Species of Phalaris hold significant importance as forage and weeds. Anatomical and micromorphological studies can provide diagnostic traits critical for taxonomy. In this study, we investigated the leaf sheath anatomy and the micromorphology of the lemma and palea to identify distinguishing traits among some Phalaris species in Iran. Twenty-one accessions of three Phalaris species (P. minor, P. brachystachys, and P. paradoxa) from different regions of Iran were studied. Leaf sheath cross-sections were stained using methyl green and Congo red, and both quantitative and qualitative anatomical traits were measured and evaluated. Micromorphological features of the lemma and palea were observed using a Hitachi SU3500 Scanning Electron Microscope. Eleven traits were assessed in the studied species. While the general leaf sheath anatomy showed significant similarities, micromorphological investigations of the lemma and palea epidermis highlighted the palea epidermis, the presence or absence of prickles, and papillae density as key distinguishing features. The findings are consistent with previous studies on this subfamily, enhancing the understanding of Phalaris species taxonomy.